Implementing the 2:1 student placement model in occupational therapy: Strategies for practice. (2nd February 2016) - Price, David; Whiteside, Mary
Abstract : Background/aim: Health industry changes, including a growing demand for health professionals, have led to a greater need for clinical placements for occupational therapy and other health discipline students. As we develop programmes to accommodate larger numbers of student placements, there is a need to ensure that we understand the challenges and opportunities new models of supervision present and how any difficulties might be overcome. A large occupational therapy department in metropolitan Melbourne introduced a new 2:1 (two students to one supervisor) supervision model, moving away from the traditional 1:1 (one student to one supervisor) supervision model. This exploratory study examines supervisor experience in a trial of the new model. Methods: The study adopted a social constructivist theoretical perspective and an exploratory qualitative design. Data were collected in two focus groups involving eight supervisors; one focus group was held prior to implementation of the 2:1 supervision model, and one post. A thematic analysis approach was used to identify, analyse and report patterns within the data. Findings: The 2:1 placement model presented challenges particularly in relation to ensuring a quality placement and managing two students while acknowledging there were also opportunities for peer learning. Supervisors developed a number of strategies to minimise difficulties and maximise benefits, including taking an evidence‐based approach, being prepared, mobilising organisational support and being positive but also pragmatic. Conclusions: The 2:1 student placement model is likely to be a model of choice in the future. There are challenges and opportunities associated with its use. This study identifies these as well as strategies for maximising opportunities and mitigating challenges.